RAMAN STUDY OF HIGH-PRESSURE PHASE TRANSITIONS IN DEHYDRATED ANALCIME - Miroshnichenko Yu.M.; Goryainov S.V. (My University, 2000)
The high-pressure behaviour (up to 30 kbar) of dehydrated analcime, Na[AlSi 2 O 6 ), has been studied in detail using polarized microscopy and Raman micro-spectroscopy. Samples were compressed using a diamond anvil cell in a quasi-hydrostatic medium (glycerol or water-ice). Two transitions at 3.7 and 11 kbar were observed. At the first transition, phase II is observed under cross polarized light as a contrasting black zone, moving from the edge to the centre of the sample. At this transition the strong Raman doublet at ∼480 and 500 cm ⁻¹ transforms discontinuously to a singlet, which is similar to that of quasi-cubic natural analcime. This transition, with an increase of effective symmetry, seems unusual on increasing pressure. The analcime framework may be thought of as an array of four-, six-, or eight-membered interconnected rings. Phase transitions in the analcime group are considered in the literature in terms of deformations of the six-membered rings. However, the present work shows that these phase transitions should be associated with deformations of the four-membered rings (as the minimum size secondary building units) by rotation of rigid TO4 units. The strongest Raman band frequency is correlated with the mean T-O-T angle inside the four-membered ring: a rate of 4.5 cm ⁻¹ /degree was found for analcimes and leucites. Using this correlation, one can estimate from Raman data the possible deformation of four-membered rings at the phase transitions.